Everyday Exposure to Occupational/Non-Occupational Infrasound Noise in Our Life - Adam ZAGUBIEŃ; Katarzyna WOLNIEWICZ (Archives of Acoustics, 2016)
Infrasounds are very common in the natural environment. There are various opinions about their harmfulness or lack of harmfulness. One of the reasons of increasing interest in this issue is that there are more and more wind farms appearing close to building estates which are undoubtedly a source of infrasound. It is reasonable to present the results of research of infrasound noise connected not only with wind farms. In this study own results of research of infrasound noise related to daily human activity are presented. The measurements were carried out during housework, travel to the office or shop, and during shopping. The results are shown in the form of values of equivalent levels and 1/3-octave analyses. Taking into consideration the natural sources of infrasound in the environment, the measurements were conducted during both windy and windless weather. On the basis of the results of the measurements it was possible to define the daily exposure to infrasound noise. Those results were also compared with the available in the literature threshold values sensed by people. Estimated level of exposure to noise beyond workplace together with the level of exposure to noise at work enables to define daily exposure level, which means a better assessment of risk of health loss. Increasing social awareness of acoustic threat in everyday life allows us to identify the problem and at the same time improve the quality of rest and efficiency at work.